Environment-Driven Adaptations of Leaf Cuticular Waxes Are Inheritable for Medicago ruthenica - Guo, Yanjun; Zhao, Xiao; Li, Yang; Li, Zhen; Xiao, Qianlin; Wang, Yanmei; Zhang, Xuefeng; Ni, Yu (Frontiers in Plant Science, 2021)
Cuticular waxes covering the plant surface play pivotal roles in helping plants adapt to changing environments. However, it is still not clear whether the responses of plant cuticular waxes to their growing environments are inheritable. We collected seeds of Medicago ruthenica (a perennial legume) populations from 30 growing sites in northern China, and examined the variations of leaf cuticular waxes in a common garden experiment. Four wax genes, MrFAR3-1, MrFAR3-2, MrCER1 and MrKCS1, involved in biosynthesis of predominant wax classes (primary alcohol and alkane) and wax precursors, were isolated to test the contributions of genetic variations of the coding sequences (CDS) and the promoter sequences and epigenetic modifications. The plasticity responses of the cuticular waxes were further validated by two stress-modeling experiments (drought and enhancing UVB). Great variations in total wax coverage, abundance of wax classes or wax compounds were observed among M. ruthenica populations in common garden experiment. Stress-modeling experiments further validated that M. ruthenica would alter leaf wax depositions under changed growing conditions. The transcriptional levels of the wax genes were positively or negatively correlated with amounts of cuticular waxes. However, the analysis of promoter methylation showed that the methylation level of the promoter region was not associated with their expressions. Although both promoter sequences and CDS showed a number of polymorphic sites, the promoters were not naturally selected and insignificant difference could be observed in the numbers and types of acting elements of the four wax genes among populations. In contrast, the CDS of the wax genes were naturally selected, with a number of missense mutations resulting in alterations of the amino acid as well as their isoelectric points and polarities, which could impact on enzyme function/activity. We conclude that long-term adaptation under certain environments would induce genetic mutation of wax biosynthesis genes, resulting in inheritable alterations of cuticular wax depositions.